SURG-15. UPFRONT MRI-GUIDED STEREOTACTIC LASER-ABLATION IN NEWLY DIAGNOSED GLIOBLASTOMA: A MULTICENTER REVIEW OF SURVIVAL OUTCOMES COMPARED TO A MATCHED COHORT OF BIOPSY-ONLY PATIENTS. (5th November 2018) - Mohammadi, Alireza; Sharma, Mayur; Beaumont, Thomas; Juarez, Kevin; Kemeny, Hanna; Dechant, Cosette; Seas, Andreas; Sarmey, Nehaw; Lee, Bryan; Jia, Xuefie; Fecci, Peter; Baehring, Joachim; et al.
Abstract: BACKGROUND: Laser ablation (LA) is used as an upfront treatment in patients with deep seated newly diagnosed Glioblastoma (nGBM). We evaluated the outcomes of LA in patients with nGBM and compared them with a matched biopsy-only cohort. METHODS: 24 nGBM patients underwent upfront LA at Cleveland Clinic, Washington University in St. Louis and Yale University (6/2011–12/2014) followed by chemo/radiotherapy (CRT). Also, 24 out of 171 nGBM patients with biopsy from Duke and Yale Universities who followed by CRT were matched with our LA cohort based on age (<70 vs 70), gender, tumor location (deep vs lobar) and volume (<11 cc vs 11 cc). Progression-free survival (PFS), overall survival (OS), disease-specific PFS and OS ((DS-PFS, DS-OS) were our endpoints. Three prognostic groups were identified based on extent of tumor ablation by thermal-damage-threshold (TDT)-lines. RESULTS: The median tumor volume in LA (n=24) and biopsy only (n=24) groups was 9.3 cm3 and 8.2 cm3 respectively. Overall, median estimate of OS and PFS in LA cohort was 14.4 and 4.3 months compared to 15.8 months and 5.9 months for biopsy only cohort. On multivariate analysis, favorable TDT-line prognostic groups were associated with lower incidence of disease specific death (p=0.03) and progression (p=0.05) compared to other groups including biopsy only cohort. Only age (<70 years, p=0.02) and tumor volume (<11 cc, p=0.03) were favorable prognostic factors for OS. CONCLUSIONS: The maximum tumor coverage by laser ablation followed by radiation/chemotherapy is an effective treatment modality in patients with newly diagnosed GBM who are not a candidate for standard craniotomy, compared to biopsy only cohort. The TDT-line prognostic groups were independent predictor of disease specific death and progression after laser ablation.